Implementasi Pembangkit Pn Panjang-Maksimal Termodifikasi Dan Akuisisinya Dengan Pencarian Serial - Perpustakaan UGM, i-lib ([Yogyakarta] : Pusat Studi Energi UGM, 2005)
ABSTRAK There are two kinds of binary codes applied in recent cellular code division multiple access (CDMA) technologies: orthogonal codes and pseudo-random (PR) or pseudo-noise (PN) codes. The receiver must generate the same codes, which are replica of those used by the appropriate transmitter. This research implemented a modified (2N, not 2N â 1) maximal-length PN-code generator and its acquisition circuit. These PN-codes were generated using a modified linear feedback shift register (LFSR) configuration, and the acquisition circuit was based on the serial-search method. -The implemented system consisted of a transmitter and a receiver. The transmitter generated two 64-chip-long different PN-codes. These two codes represented two separate synchronous channels. The receiver performed the acquisition of one of these two channels. The results show that the system has operated properly and can be used to demonstrate the PN-code generation and acquisition, with the chip-rate of about 307 kcps or lower. Keywords: Pembangkit semu, sistem selular CDMA